Penerapan Model Pembelajaran Kooperatif Teknik Think Pair Square (TPS) untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas XII IPS 2 SMA Negeri 1 Bangko Kabupaten Rokan Hilir - Halimah Tusaddiah (Journal on Education, 2021)
This study aims to provide an overview that the application of the Think Pair and Square (TPSq) Cooperative Learning Model can improve student learning at probabilities subject in Class XII IPS2 SMAN 1 BANGKO Rokan downstream. This research is a classroom action research (CAR) which is carried out in 2 cycles. For learning outcomes in the first cycle, 37.5% of students reached the KKM and in the second cycle, 54.2% of students reached the KKM. The basic score of students who reach the KKM is 29.2%. The basic score in this study is the daily test score on the previous subject, namely statistics. The conclusion obtained from this study is that the application of the Think Pair Square Cooperative Learning Model can improve student learning outcomes.